ANALISIS PEMAHAMAN MAHASISWA PGMI SEMESTER 4 INSTITUT AGAMA ISLAM NGAWI 2025/2026 TERHADAP MATERI PENGEMBANGAN ASPEK KOGNITIF ANAK SEKOLAH DASAR - Ningrum Puji Lestari; Anis Satul Mufidah; Ridho Imam (CV. Denasya Smart Publisher, 2025)
The purpose of this study is to analyze the level of understanding among fourth-semester students of the Primary School Teacher Education Program at the Institute of Islamic Religion Ngawi for the academic year 2025/2026 regarding the development of cognitive aspects in elementary school children. Understanding cognitive aspects is crucial in the learning process as it relates to children's abilities to think, remember, and solve problems. This study employs a descriptive quantitative method, using a questionnaire as the instrument distributed to fourth-semester students of the PGMI Program at the Institute of Islamic Religion Ngawi as respondents. The results of the study indicate that the respondents generally have a high level of understanding, particularly concerning the stages of child development in elementary school, the role of teachers in cognitive development, and the importance of instructional adaptation.